The risk of Clostridium difficile infection in patients with pernicious anaemia: a retrospective cohort study using primary care database. - Othman, Fatmah; Crooks, Colin J.; Card, Timothy R. (SAGE, 2017)
Background: Studies have found an association between proton pump inhibitor (PPI) use and Clostridium difficile infection. The purpose of this study was to determine whether the mechanism by which PPIs induce an increased risk of C. difficile infection is supported by the same mechanism acting in another cause of achlorhydria, pernicious anaemia. Methods: Using a database of anonymised primary care records between 1990 and 2013, we selected exposed patients with a diagnosis of pernicious anaemia treated with vitamin B12 therapy. Each exposed patient was matched by age, gender and general practice to up to 10 controls. Cox regression analysis was used to estimate the hazard ratio (HR) and 95% confidence interval (CI) for C. difficile infection with pernicious anaemia, adjusted for potential confounders. Results: We identified 45,467 exposed patients matched to 449,635 controls. The crude incidence rate of C. difficile infection was 1.85/1000 person-years for the exposed cohort and 1.09/1000 person-years for controls. Patients with pernicious anaemia had a greater risk of C. difficile infection than the controls (adjusted HR 1.57, 95% CI 1.40–1.76). Conclusions: Pernicious anaemia patients have an increased risk of C. difficile infection. This supports the theory that severe achlorhydria is the mechanism that increases the risk of C. difficile infection in long-term PPI users.